Devotion, Theology and the Sensus Fidelium - Llywelyn, Dorian (New blackfriars, 2017)
The potential unwieldiness of popular religiosity and devotional spirituality and their ambiguous relationship with the liturgy have made them objects of perennial ecclesiastical concern. More recently, magisterial discussion of popular religiosity has come to value more positively its cultural and anthropological value and its spiritual content. The reforms of Vatican II were followed by a significant demise in devotionalism amongst Northern European and North American Catholics, yet demographic change and other factors have resulted in the resurgence of popular religious devotions. Manifestations of grassroots faith may express valuable convictions and important insights, including the value of the collective and the non-verbal. However, these values may be easily dismissed by social elites for aesthetic reasons, or by academic theologians for reasons of the cultural milieu and preferences of academia. Given the preference of the theological tradition for lexical intelligibility, and the symbolic and the physical nature of many kinds of popular religiosity, how the sub-disciplines of theology may now responsibly and respectfully treat these perduring phenomena is not clear. A healthy relationship between the fides qua and the fides quae demands taking seriously the sensus fidelium, understood as a broad experience that embraces the daily lives and local circumstances of Christians as well as their worship. The contemporary construal of the discipline of Christian Spirituality, understood as the study of Christian experience, promises to provide a multidisciplinary approach that can address the topic of popular religiosity and devotional practice.